Blanded Learning Sebagai Alternatif Model Pembelajaran dalam Meningkatkan Hasil Belajar Siswa di Madrasah - Ni’mah, Fithratu; Mislikha; Sofyan, Hadi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The teacher's WA group allows students to send files in the form of text, and videos, and even make group video calls, making it possible to maximize the use of WA and Google Meet groups in the delivery of material in this online class. The blended learning learning model is an innovative learning model that combines the use of technology in online classes and offline (face-to-face) classes. A requirement for madrasas in RI. era 4.0 is the renewal of learning models because madrasas are Islamic educational institutions whose existence is crucial because they are institutions that teach the fundamentals of Islamic knowledge that must be transmitted and followed by all generations of Muslims. This learning strategy attempts to achieve a more ideal meaning, especially in Fiqh subjects, which are significant in Islamic education and can be used as supplementary time, requiring only two hours of lectures or one face-to-face meeting per week. Study to make it simpler to accomplish learning goals. Additionally, a qualitative descriptive research approach is used in this study. The researcher discusses how the blended learning strategy was planned, put into practice, and evaluated in order to enhance student learning outcomes at MTs Miftahul Ulum Pandanwangi Tempeh Lumajang. The purpose is to describe how MTs Miftahul Ulum, which utilized a blended learning methodology, was implemented.